RESPONS PERTUMBUHAN TEMBAKAU DELI (Nicotiana tabaccum (L.)) PADA BEBERAPA JENIS KAPUR DAN TANAH DI SUMATERA UTARA - M. Silaban, Martua; Ginting, Jonis; Barus, Asil (Universitas Sumatera Utara, 2013)
Response of growth of deli tobacco (Nicotiana tabaccum (L.)) on some kind of lime and soil typesin North Sumatera. Deli tobacco is variety of tobacco that is used as world top quality wrapper ofcigar . But, in last years production of deli tobacco had been decreasing because of landdegradation. Consequently, it is important to develop deli tobacco plantation to another soil typesthat is combine by giving some kind of lime. The aim of this research was to examine growth ofdeli tobacco (Nicotiana tabaccum (L.)) on some kind of lime and soil types in Noerth Sumatera.The research was conducted in the land of the Research Center of Deli Tobacco (BPTD) SampaliPTPN II, starting from February to May 2012, using a randomized block design (RBD) factorialwith two factors and three replications . The first factor is soil types (alluvial, andosol, hidromorf,ultisol). The second factor is the kind of lime (dolomite, calsit, kaptan). The results showed thatsoil types significantly affect on plant height, diameter of stem, number of leave, thick leaf sand,1 foot thick leaves, long leaves sand, 1 foot long leaves, leaf width sand, and 1 foot wide leaves.Kind of Lime and the interaction between soil and lime is not significantly affect for all parameterobserved.Keywords: soil, lime, Tobacco Deli.